Revealing Rape's Many Voices Differing Roles, Reactions and Reflections - Brown, Jennifer; Shell, Yvonne; Cole, Terri (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This book gives voice not only to rape survivors but also to the perspectives of the many 'others'- both inside and outside the criminal justice system. The concept of 'the rape sphere' presents an important contribution in providing a framework to unpack the complex, overlapping, and wide-reaching impacts resulting from a rape." -Debra Langan, Associate Professor of Criminology, Wilfrid Laurier University, Canada "Rape is like a grenade. The shrapnel hits everybody, exploding in the family home, friendship groups, work colleagues, neighbours, even the neighbourhood itself. I feel this book goes a long way to explaining the issues faced and how professionals can help deal with them." -Martyn Underhill MBE, Retired Detective Chief Inspector, and Police and Crime Commissioner, 2012-21, Dorset, UK By extending the cast list of roles implicated in rape's hidden sphere of harm, this book attentively listens toexperiential voices of complainant/witnesses, suspect/accused, police, lawyers, judges and jurors, therapists, advocates, partners, parents, family and friends during the criminal justice journey. Highlighting good and bad practices, it proposes a paradigm shift for inculcating policy reform, arguing the case for implementation science as a framework for embedding change. The book will be of interest to those involved in the policy, practice and delivery of criminal justice, the support and voluntary sector as well as giving valuable insights to students of forensic and investigative psychology, criminology, law, social policy, gender studies and also those studying on the new policing apprenticeship degree programmes. Jennifer Brown is a visiting professor at the Mannheim Centre, London School of Economics and Political Science, UK. She recently co-edited a second edition of Rape: Challenging Contemporary Thinking (Routledge). Yvonne Shell is dually qualified as Registered Clinical and Forensic Practitioner Psychologist and Chartered Psychologist specialising in assessment and treatment of forensic clients. Terri Cole, formerly a behavioural investigative adviser, is currently the Principal Academic in Forensic Psychology leading an Investigative Forensic Psychology master's programme at Bournemouth University, UK.
SECTION 1: INTRODUCTION -- Chapter 1: Overview -- Chapter 2: Hearing and listening -- SECTION 2: THE ADVERSARIES -- Chapter 3: The complainant/witness -- Chapter 4: The suspect/accused/defendant -- SECTION 3: THE PROFESSIONALS -- Chapter 5: The investigators -- Chapter 6: The lawyers -- Chapter 7: The judge and jury -- SECTION 4: SUPPORT AND ADVOCACY -- Chapter 8: Practitioners -- Chapter 9: Partners, friends and family -- SECTION 5: THE AFTERMATH -- Chapter 10: The victim/survivor -- Chapter 11: The offender/acquitted -- Chapter 12: Where do we go from here?.
Keywords: Criminal behavior; Victims of crimes; Critical criminology; Forensic psychology; Social policy; Sex; Criminal Behavior; Victimology; Critical Criminology; Forensic Psychology; Social Policy; Gender Studies